2008
DOI: 10.4191/kcers.2008.45.8.439
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Electrical and Mechanical Properties of Reaction-Sintered SiC by using Different-Sized SiC Particles in Preform

Abstract: A series of reaction-sintered SiC was fabricated from preforms with varying volume fractions of two resin-coated SiC particles of different sizes (63 and 18 µm). The electrical resistivity and mechanical strength were eventually optimized at the small particle volume fraction of 0.3~0.4, at which point the porosity of the preform was minimized. This study experimentally proves that additional processes after the formation of the preform, such as silicon infiltration and reaction sintering, do not apparently al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Recently, the current research group reported that residual silicon can be eliminated by a post process such as evaporation at temperatures higher than those of the reaction sintering. 9,10) For the initial fast rising of temperature by joule heating of a SiC igniter, a decreased electrical resistivity is highly important. In this regard, nitrogen doping can be a good approach.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the current research group reported that residual silicon can be eliminated by a post process such as evaporation at temperatures higher than those of the reaction sintering. 9,10) For the initial fast rising of temperature by joule heating of a SiC igniter, a decreased electrical resistivity is highly important. In this regard, nitrogen doping can be a good approach.…”
Section: Introductionmentioning
confidence: 99%